The Relationship between the Role of Health Workers and Family Support in the Detection of Development and Development in children - Ria Angelina Marbun (Healthy-Mu Journal, 2021)
Toddler age is a period that lasts quickly and will not be repeated, so it is called the golden age. The incidence of growth and development disorders is currently quite high in Indonesia. The impact of not doing growth and development checks is that they cannot detect growth and development deviations in toddlers so that there are permanent deviations. The research objective was to analyze the relationship between the role of health workers and family support in early detection of toddler song development. This type of quantitative research with analytic survey design. This study used a cross sectional approach, with the sampling used was purposive sampling technique. The results of the research on the variable role of health workers obtained a positive role as many as 49 people (55.1%), while the variable family support for respondents who supported as many as 52 people (58.4%). The statistical test results obtained by the value of p = 0.013, it can be concluded that there is a significant relationship between the role of health workers and family support in early detection of toddler growth and development. Research on the provision of early stimulation in the first year of life is effective in increasing the mental and psychomotor development index of infants. In addition, the presence of children who experience delays during their growth and development can be caused by a lack of parental care in stimulating their growth and development. The research suggest the need for an increase in training programs in the detection of growth and development, programs routed by families and even visits to PAUD / kindergartens online or in person.